Llama Llama mad at mama - Dewdney, Anna. (New York : Viking, 2007)
A young llama wants to play but must go shopping with his mother instead, and so he gets angry and makes a mess at the store.
Keywords: Mother and child -- Juvenile fiction; Shopping -- Juvenile fiction; Llamas -- Juvenile fiction; Stories in rhyme -- Juvenile fiction